Saturated pool boiling enhancement using porous lattice structures produced by Selective Laser Melting - Wong, Kin Keong (2019)
Pool boiling heat transfer of saturated FC-72 under atmospheric pressure was studied for porous lattice structures fabricated using the Selective Laser Melting (SLM) technique. The substrates possess repeating geometry of octet-truss unit cell and were varied with unit cell sizes of 2.0 mm, 3.0 mm and 5.0 mm and structure heights of 2.5 mm, 5.0 mm and 10.0 mm. In comparison with a plain surface, the porous structures show significant enhancement in nucleate boiling heat transfer coefficients and delay of Critical Heat Flux (CHF). The enhancement is attributed to the increased surface area, increased nucleation site density and capillary-assisted suction of the porous structure. The porous structure allows sustained liquid replenishment which delayed the hydrodynamic choking and CHF significantly. The best performing substrate with the 3-mm unit cell size and 5-mm structure height has an average nucleate boiling heat transfer coefficient of 1.35 W/cm2·K, which is 2.81 times that of the plain surface at 0.48 W/cm2·K. Heat transfer mechanisms are proposed for the different heat flux levels of the porous structures based on visual observations. The boiling patterns are classified as low, mid, high and very-high heat flux levels. At high heat flux level, two separate modes of stable and unstable boiling patterns are observed. For the stable boiling pattern, there are distinct bubble departure and liquid replenishment pathways, thus allowing a good convection flow. However, for the unstable boiling pattern, there is major liquid–vapor counter-flow, which disrupts the orderly liquid replenishment pathway.